(untitled) (Revista de Educação Pública, 2013)
The Revista de Educação Pública - ISSN 0104-5962 - E-2238-2097 – is a quarterly publication articulated to the Postgraduate Program in Education of Universidade Federal de Mato Grosso. It publishes articles in education field, as well as essays and reviews papers that privilege works in education. The essays are intended only to theoretical and methodological which are relevant to the journal’s sections. Studies on the state of the art about issues in education area are also accepted.